2011
DOI: 10.1501/vetfak_0000002445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic and prebiotic (mannanoligosaccharide) supplementation on performance, egg quality and hatchability in quail breeders

Abstract: Summary:This study was performed to investigate the effects of probiotic and prebiotic (mannanoligosaccharide) supplementation on performance, egg quality and hatchability in quail breeders. Four hundred and eighty, 18 wk old Japanese quail (Coturnix coturnix japonica) were evenly distributed to 5 groups with four replicates containing 24 (18 female, 6 male) quail in each. Quail were fed either basal diet (control group) or 0.5 and 1 kg/ton probiotic and prebiotic supplemented basal diets (treatment groups) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…The tendency of higher egg production was observed in the MOSsupplemented groups, but not in the control group; however, it was statistically not significant. Similar results were found by Tarasewicz et al (2004), Güçlü (2011), andBozkurt et al (2012), who reported that oligosaccharides-supplemented diet increased the capacity of egg production. Increased egg production by MOS supplementation might be due to an increase in the intestinal length of birds, reduction of pathogens, and increased beneficial bacteria, which ultimately enhanced the absorptive ability of the intestine (Chen et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The tendency of higher egg production was observed in the MOSsupplemented groups, but not in the control group; however, it was statistically not significant. Similar results were found by Tarasewicz et al (2004), Güçlü (2011), andBozkurt et al (2012), who reported that oligosaccharides-supplemented diet increased the capacity of egg production. Increased egg production by MOS supplementation might be due to an increase in the intestinal length of birds, reduction of pathogens, and increased beneficial bacteria, which ultimately enhanced the absorptive ability of the intestine (Chen et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Abd El-Samee et al (2012) observed that egg weight of quails was significantly higher in MOS-supplemented group than in the control. However, Bonos et al (2011) andGüçlü (2011) could not find significant effects of MOS on egg weight of birds.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When MOS was used as a food supplement, animal weight and survival ratio were significantly increased. (Savage & Zakrzewska, 1996 Murray & Ivey, 1997;Kaufhold, Hammon, & Blu m, 2000;Heinrichs, Jones, & Heinrichs, 2003;Sarıkaya & Küçük, 2009;Kahraman, Mızrak, Yenice, Atik, & Tunca, 2010;Güçlü, 2001, Yalçinkaya, Gungor, Bafialan, & Erdem, 2011. MOS has also been used in aquaculture by many authors.…”
Section: Introductionmentioning
confidence: 99%